Karakteristik Fisikokimia dan Sensori Minuman Jelly Sambiloto (Andrographis paniculata) dengan Variasi Formulasi - Fitriyani .; Noli Novidahlia; Distya Riski Hapsari (Jurnal Pangan dan Gizi, 2026)
Jelly drinks are a type of beverage with a semi-liquid consistency (firm yet tender) made from hydrocolloid ingredients and water. This study aimed to investigate the impact of various sambiloto jelly drink formulations on the product's physicochemical and sensory characteristics. The research utilized a Completely Randomized Design (CRD) with a single factor variable consisting of four sambiloto jelly drink formulations (A1, A2, A3, A4), each replicated twice. Product analysis was performed using ANOVA at a 95% confidence level (α=0.05), which included syneresis, pH, and total solids, while the non-parametric Friedman test was utilized for sensory evaluation. The results showed that variations in the sambiloto jelly drink formulations significantly affected syneresis value (12,98%), pH (5,137), total solids (18,12%), and the sensory quality of color, characteristic sambiloto aroma, sweetness, bitterness, and ease of consumption. Additionally, these variations influenced the hedonic attributes of aroma, taste, aftertaste, and overall acceptability, but did not impact the hedonic qualities of color and texture. Based on the De Garmo test, the optimal product was selected with a value of 0.620. This was for the sambiloto jelly drink with a formulation of 79.6g of sambiloto, 0.4g of carrageenan, 20g of honey, and 0g of water. This specific formulation exhibited the following characteristics: a syneresis value of 12.98%, a pH of 5.137, and a total solids content of 18.12%.